2014
DOI: 10.4028/www.scientific.net/amr.1049-1050.983
|View full text |Cite
|
Sign up to set email alerts
|

Review of Fractional Order Control

Abstract: With the development of mathematical theory of fractional order, fractional order control system is more widely studied and discussed. In order to make the theory system of fractional order control systems perfect,this paper give out the review of fractional order control systems.The fractional order controller is divided into five categories to be described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Control of nonlinear systems, especially chaotic systems, has been studied with growing interest in recent years (Singh and Roy, 2017, 2018; Singh et al, 2018). As stated in Leng et al (2014), various publications have appeared over the recent years. By using fractional calculus (FC), many complex dynamics can be qualified as the simple system comprising fractional-order (FO) derivatives (Bagley and Torvik, 1983; Haghighi and Roohi, 2012; Petras, 2011; Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Control of nonlinear systems, especially chaotic systems, has been studied with growing interest in recent years (Singh and Roy, 2017, 2018; Singh et al, 2018). As stated in Leng et al (2014), various publications have appeared over the recent years. By using fractional calculus (FC), many complex dynamics can be qualified as the simple system comprising fractional-order (FO) derivatives (Bagley and Torvik, 1983; Haghighi and Roohi, 2012; Petras, 2011; Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent advantages of applied fractional-order differintegrals are widely proven in process control as shown by multiple comprehensive review papers on the fractional-order PID controller [ 6 , 42 , 43 ] and complex system modeling in biomedical processes [ 2 ] through complex anomalous diffusion [ 9 ]. However, during recent years different fields such as fractional-order circuits had undergone the possible integration of fractional operators.…”
Section: Fractional-order Sensingmentioning
confidence: 99%
“…Autotuning methods for fractional order PID controllers were also proposed [21][22][23]. Some rather recent review papers on fractional order controllers can be found in [24][25][26] and provide an insight into fractional order control of different types. An excellent review paper on fractional order controllers, including their most widely used continuous and discrete approximation methods, as well as their digital and analogue implementation methods.…”
Section: Introductionmentioning
confidence: 99%